My first picture encyclopedia - Parker, Steven (Bath [UK] Parragon, 2007)
My First Picture Encyclopedia is a comprehensive introduction to the world in which we live. Children can read about a huge range of topics, from the coulourful world of animals and plants to the mysteries of science and outer space. This is the perfect reference tool for young readers who are hungry for knowledge.